ABO blood group is associated with peripheral arterial disease in African Americans: The Multi-Ethnic Study of Atherosclerosis (MESA). Issue 153 (May 2017) - Pike, Mindy M.; Larson, Nicholas B.; Wassel, Christina L.; Cohoon, Kevin P.; Tsai, Michael Y.; Pankow, James S.; Hanson, Naomi Q.; Decker, Paul A.; Berardi, Cecilia; Alexander, Kristine S.; Cushman, Mary; Zakai, Neil A.; et al.
Abstract: Introduction: Peripheral artery disease (PAD) affects 8.5 million Americans and thus improving our understanding of PAD is critical to developing strategies to reduce disease burden. The objective of the study was to determine the association of ABO blood type with ankle brachial index (ABI) as well as prevalent and incident PAD in a multi-ethnic cohort. Methods: The Multi-Ethnic Study of Atherosclerosis includes non-Hispanic White, African, Hispanic, and Chinese Americans aged 45–84. ABO blood type was estimated using ABO genotypes in 6027 participants who had ABI assessed at the baseline exam. Associations with ABO blood type were evaluated categorically and under an additive genetic model by number of major ABO alleles. After excluding those with ABI > 1.4, prevalent PAD was defined as ABI ≤ 0.9 at baseline and incident PAD as ABI ≤ 0.9 for 5137 participants eligible for analysis. Results: There were 222 prevalent cases and 239 incident cases of PAD. In African Americans, each additional copy of the A allele was associated with a 0.02 lower baseline ABI ( p  = 0.006). Each copy of the A allele also corresponded to 1.57-fold greater odds of prevalent PAD (95% CI, 1.17–2.35; p  = 0.004), but was not associated with incident PAD. No associations were found in other racial/ethnic groups for ABI, prevalent PAD, or incident PAD across all races/ethnicities. Conclusions: Blood type A and the A allele count were significantly associated with baseline ABI and prevalent PAD in African Americans. Further research is needed to confirm and study the mechanisms of this association in African Americans. Highlights: Risk of lower-extremity atherosclerosis differs by blood type. Type A was associated lower ankle brachial index in African Americans. Each copy of the A allele corresponded to 1.57-fold greater odds of PAD.